2016
DOI: 10.1093/mnras/stw3277
|View full text |Cite
|
Sign up to set email alerts
|

Dark jets in the soft X-ray state of black hole binaries?

Abstract: X-ray binary observations led to the interpretation that powerful compact jets, produced in the hard state, are quenched when the source transitions to its soft state. The aim of this paper is to discuss the possibility that a powerful dark jet is still present in the soft state. Using the black hole X-ray binaries GX339-4 and H1743-322 as test cases, we feed observed X-ray power density spectra in the soft state of these two sources to an internal shock jet model. Remarkably, the predicted radio emission is c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 59 publications
0
16
0
Order By: Relevance
“…In the soft X-ray state instead, jets appear to be quenched at all frequencies (see, e.g., Russell et al 2011) in favor of disk winds (Ponti et al 2012), probably due to the suppression of the magnetic field caused by the geometrically thin accretion disk that resides close to the BH (see, e.g., Meier 2001). Alternatively, in line with the internal shock model for BHB jets by Malzac (2013), during the soft state, the jet might still be present but is dark because of the lack of variability in the disk (Drappeau et al 2017). In some cases, the jet break frequency has been found to move from infrared to radio frequencies as the X-ray spectrum of the source softens, and then come back again to the infrared band at the end of the outburst, when the spectrum gets harder (Russell et al 2013a(Russell et al , 2014Diaz Trigo et al 2018).…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…In the soft X-ray state instead, jets appear to be quenched at all frequencies (see, e.g., Russell et al 2011) in favor of disk winds (Ponti et al 2012), probably due to the suppression of the magnetic field caused by the geometrically thin accretion disk that resides close to the BH (see, e.g., Meier 2001). Alternatively, in line with the internal shock model for BHB jets by Malzac (2013), during the soft state, the jet might still be present but is dark because of the lack of variability in the disk (Drappeau et al 2017). In some cases, the jet break frequency has been found to move from infrared to radio frequencies as the X-ray spectrum of the source softens, and then come back again to the infrared band at the end of the outburst, when the spectrum gets harder (Russell et al 2013a(Russell et al , 2014Diaz Trigo et al 2018).…”
Section: Introductionmentioning
confidence: 93%
“…Similar to what was suggested by Gandhi et al (2010), a model that relates possible perturbations in the accretion flow to variability in the jet might explain the observed variability of our light curves. Such a model has been developed in Malzac (2013) and Malzac (2014; see also Drappeau et al 2017). In this scenario, a strongly variable accretion flow could inject nonnegligible velocity fluctuations at the base of the jet, which would drive internal shocks at large distances from the BH, where leptons are accelerated, giving rise to strongly variable synchrotron emission, which would in turn affect the radio-infrared emission of the system.…”
Section: Short Time Variability: Possible Interpretationmentioning
confidence: 99%
“…Drappeau et al (2015) first explored this idea by using the internal shock code ishem (Malzac 2014) to show that an observed radio-IR jet SED from the black hole binary GX 339-4 during the hard state can be well reproduced, under the assumption that the power spectrum of the jet fluctuations is identical to the fluctuations in the disc observed in X-rays. Drappeau et al (2017) suggested that the quenching of the radio emission in the soft X-ray spectral state could be associated with the much weaker X-ray variability present in this state. Dark jets could be present in the soft state carrying a similar power as in the hard state, but weaker shocks due to the smaller amplitude of the velocity fluctuations mean the jet would be undetectable.…”
Section: Introductionmentioning
confidence: 99%
“…The internal shock model has initially been invoked by Rees (1978) to explain the emissions by the knots in the jets of active galactic nuclei and the internal shock model also explains the prompt emissions of gamma-ray bursts (Piran 1999(Piran , 2004. Malzac (2014) and Drappeau et al (2015) have examined to what extent the emissions of the relativistic jets of microquasars can be explained by internal shocks.…”
Section: Introductionmentioning
confidence: 99%